2013
DOI: 10.5348/ijcri-2013-05-305-cr-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism diagnosed immediately following blunt trauma

Abstract: Introduction: Physicians who care for trauma patients should be aware of the possibility of a pulmonary embolism presenting immediately after traumatic injury. Case Report: We report a case of a 30yearold female restrained driver who developed a pulmonary embolism within two hours of a motor vehicle accident. Conclusion: We conclude that trauma can produce a hypercoagulable state that can occur immediately after a traumatic event and result in a pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…Several studies have suggested that immediate PE may be not be related to DVT and may exist as a separate entity that arises in the lungs de novo following traumatic injury. [9][10][11] In keeping with this theory, most immediate PEs in our study, as in other reports [17,18] were diagnosed within hours of injury, with minimal time for a DVT to form and generate emboli. Chest and limb injuries were more frequently associated with immediate PE than pelvic injuries, which does not fit with the classic reports of PE development following trauma but suggests an interesting hypothesis about the mechanism of formation of immediate PE: inflammation related to direct chest injury and autonomic dysfunction leading to vasospasm and thrombosis have been suggested as potential contributors to immediate PE pathophysiology following trauma, [18] a consequence of the amount of kinetic energy transmitted across the chest.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several studies have suggested that immediate PE may be not be related to DVT and may exist as a separate entity that arises in the lungs de novo following traumatic injury. [9][10][11] In keeping with this theory, most immediate PEs in our study, as in other reports [17,18] were diagnosed within hours of injury, with minimal time for a DVT to form and generate emboli. Chest and limb injuries were more frequently associated with immediate PE than pelvic injuries, which does not fit with the classic reports of PE development following trauma but suggests an interesting hypothesis about the mechanism of formation of immediate PE: inflammation related to direct chest injury and autonomic dysfunction leading to vasospasm and thrombosis have been suggested as potential contributors to immediate PE pathophysiology following trauma, [18] a consequence of the amount of kinetic energy transmitted across the chest.…”
Section: Discussionsupporting
confidence: 90%
“…[7][8][9] Intriguingly, several studies have reported the presence of thrombus in the pulmonary circulation within the first few hours of traumatic injury, which has given rise to the concept of immediate PE (or de novo intrapulmonary thrombus) postulated to exist separately from classical PE. [10,11] The role for anticoagulation when PEs present in this way, particularly in the presence of co-existent traumatic haemorrhagic lesions, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Upon literature review, there is only one case reported the association between trauma and PE in 2013 a young female presented 1 h after a motor vehicle accident with chest pain and turned to be PE. However, she was using contraceptive pills 16 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Henry et al (37) worked on pelvic fracture in geriatric patients; his results showed that the incidence of proximal deep vein thrombosis with pelvic fractures was 25-35%.and the incidence of symptomatic pulmonary embolism was 2-10% deducing that thromboembolism was the most common complication following pelvic fractures. In the same context Lewis et al (38) explained that trauma can produce a hypercoagulable state immediately after a traumatic event resulting in a pulmonary embolism on his work on the same subject. On the contrary .…”
Section: Number Of Patientsmentioning
confidence: 97%